Method for treating organic wastewater by advanced oxidation

CN121020790BActive Publication Date: 2026-10-09CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410660425.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-27
Publication Date
2026-10-09
Estimated Expiration
2044-05-27

AI Technical Summary

Technical Problem

上述方法将铜离子与载体紧密结合,虽然缓解了铜离子的流失,但催化剂的催化活性会受到影响

Benefits of technology

[0024]与现有技术相比,本发明提供的有机废水高级氧化处理方法具有如下几方面优点中的一种或几种:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121020790B_ABST
    Figure CN121020790B_ABST
Patent Text Reader

Abstract

The application discloses a kind of organic wastewater advanced oxidation treatment methods, the treatment method includes the following contents: in the presence of oxygen-containing gas, organic wastewater enters wet oxidation reactor and carries out reaction, according to the contact order with organic wastewater, copper system catalyst and catalytic oxidation catalyst are sequentially filled in wet oxidation reactor.The provided treatment method process can solve the problem of copper-based catalyst metal loss while realizing efficient removal of organic matter.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of wastewater treatment technology, and in particular relates to a method for treating organic wastewater using advanced oxidation. Background Technology

[0002] With increasing national policy and regulatory focus on environmental issues, the treatment of organic wastewater has become a hot topic in my country's wastewater treatment field. High-concentration, recalcitrant organic wastewater is difficult to treat effectively using conventional methods. For example, incineration, a commonly used method, is energy-intensive, expensive, and prone to secondary pollution. Catalytic wet oxidation is an effective method for treating high-concentration, recalcitrant organic wastewater. Commonly used catalysts are divided into two categories: precious metals and non-precious metals. Precious metal catalysts use platinum, rhodium, ruthenium, palladium, gold, and silver as active components. However, precious metals are scarce and expensive, making them suitable only for special applications. Non-precious metal catalysts commonly use copper, iron, and manganese as active components. However, under wet oxidation conditions, these active components are extremely prone to dissolution, leading to loss and waste of the catalyst's active components and causing secondary pollution.

[0003] Currently, the main solution in this technical field is to suppress the dissolution of copper ions by enhancing the binding ability between the active component (copper element) and the carrier. CN111056612A discloses a method and application for treating sulfur-containing wastewater. This method involves wet oxidation treatment of sulfur-containing wastewater in the presence of a catalyst and an oxidant, wherein the catalyst is a copper-based spinel catalyst. This invention uses a copper-based spinel catalyst to treat sulfur-containing wastewater, such as alkaline slag wastewater, through wet oxidation. Under relatively mild treatment conditions, the reducing sulfides in the sulfur-containing wastewater are essentially converted into sulfates, and the catalyst is stable, has good acid and alkali resistance, and is not easily lost. CN108940301A discloses a wet oxidation catalyst and its preparation method. This method involves sequentially mixing and precipitating an activated alumina slurry with a copper source precursor, a cerium source precursor, and a manganese source precursor to ultimately form a wet oxidation catalyst. The catalyst can be recycled and reused, effectively reducing the loss of copper ions. The above method tightly binds copper ions to the support, which alleviates the loss of copper ions, but the catalytic activity of the catalyst will be affected.

[0004] Advanced oxidation technologies can fully utilize transition metal ions as homogeneous catalysts, resulting in good treatment effects for organic wastewater. Therefore, improving the treatment efficiency of organic wastewater and solving the problem of secondary pollution caused by metal ion leaching, based on the high activity of copper-based catalysts and advanced oxidation processes, is a promising research direction in this field. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the main objective of this invention is to provide an advanced oxidation treatment method for organic wastewater. The provided treatment method can achieve efficient removal of organic matter while solving the problem of metal loss from copper-based catalysts.

[0006] The first aspect of the present invention provides a method for advanced oxidation treatment of organic wastewater according to a first embodiment. The method includes the following steps: under the condition of the presence of oxygen-containing gas, organic wastewater enters a wet oxidation reactor for reaction, and copper-based catalyst and catalytic oxidation catalyst are sequentially loaded into the wet oxidation reactor in the order of contact with the organic wastewater.

[0007] The second embodiment of the present invention provides an advanced oxidation treatment method for organic wastewater, the treatment method comprising the following steps: under the presence of oxygen-containing gas, organic wastewater enters a wet oxidation reactor for reaction; according to the contact sequence with the organic wastewater, a copper-based catalyst and a catalytic oxidation catalyst are sequentially loaded into the wet oxidation reactor; the liquid phase stream obtained after treatment by the wet oxidation reactor contacts the oxidant for reaction; after the reaction is completed, the pH value of the system is adjusted to be not less than 7 and sedimentation treatment is performed.

[0008] In a preferred embodiment, in the above-mentioned advanced oxidation treatment method for organic wastewater, the COD value of the organic wastewater is 5000-50000 mg / L, and the organic wastewater can be any one or more of refining wastewater, chemical wastewater, and municipal wastewater.

[0009] In a preferred embodiment, in the above-mentioned advanced oxidation treatment method for organic wastewater, the oxygen-containing gas has an oxygen volume content of 20% to 100%; specifically, the oxygen-containing gas can be selected from at least one of air, oxygen, and a mixture of oxygen and an inert atmosphere, wherein the inert atmosphere can be nitrogen and / or an inert gas. In a further preferred embodiment, the oxygen-containing gas is preheated with the organic wastewater before entering the wet oxidation reactor, typically to 100–200°C.

[0010] In a preferred embodiment, the reaction conditions within the wet oxidation reactor in the above-mentioned advanced oxidation treatment method for organic wastewater are as follows: reaction temperature of 150–350°C, pressure of 4–15 MPa, and space velocity of 0.25–3.0 h⁻¹. -1 .

[0011] In a preferred embodiment, in the above-mentioned advanced oxidation treatment method for organic wastewater, the amount of oxygen-containing gas used is more than 1.0 times the amount of oxidant required based on the COD value of the organic wastewater raw material.

[0012] In a preferred embodiment, in the above-mentioned advanced oxidation treatment method for organic wastewater, the oxidant is one or more of hydrogen peroxide, ozone, potassium persulfate, and persulfate, wherein the persulfate can be at least one of sodium persulfate, potassium persulfate, and ammonium persulfate; preferably, it is hydrogen peroxide, and the concentration of the hydrogen peroxide is 3wt% to 30wt%.

[0013] In a preferred embodiment, in the above-mentioned advanced oxidation treatment method for organic wastewater, the amount of oxidant used is 0.2 to 0.5 times the chemical oxygen demand of the organic wastewater.

[0014] In a preferred embodiment, in the above-mentioned advanced oxidation treatment method for organic wastewater, when the liquid phase stream obtained after treatment by the wet oxidation reactor comes into contact with the oxidant for reaction, the pH value of the reaction system is generally controlled to be 2-5. The pH value of the system can be controlled by adding an acidic compound, which is preferably an inorganic acid, specifically at least one of hydrochloric acid, sulfuric acid, and nitric acid.

[0015] In a preferred embodiment, in the above-mentioned advanced oxidation treatment method for organic wastewater, the volume ratio of copper-based catalyst to catalytic oxidation catalyst is 20%–60%: 40%–80%, preferably 30%–50%: 50%–70%.

[0016] In a preferred embodiment, in the above-mentioned advanced oxidation treatment method for organic wastewater, the copper-based catalyst includes a support and an active metal component, with the active metal component distributed on the support. The support can be selected from one or more of activated carbon, molecular sieves, and inorganic oxides. The molecular sieve is one or more of type A, type Y, Beta, ZSM-5, and TS-1 molecular sieves, and the inorganic oxide can be one or more of alumina, silicon dioxide, cerium dioxide, and titanium dioxide. The active metal component is copper, and the content of the active metal component as an oxide is 1wt% to 20wt%.

[0017] In a preferred embodiment, the above-mentioned advanced oxidation treatment method for organic wastewater further includes, optionally, an auxiliary component in the copper-based catalyst. The auxiliary component is one or more of iron, nickel, manganese, cobalt, zinc, lanthanum, cerium, tin, and molybdenum, and the content of the auxiliary component as an oxide is 0.1 to 5 wt%.

[0018] In a preferred embodiment, in the above-mentioned advanced oxidation treatment method for organic wastewater, the catalytic oxidation catalyst has a core-shell structure, wherein the core is activated carbon loaded with copper oxide and optionally ferrous sulfide, and the outer shell is silicon oxide loaded with nano-ferrous sulfide; based on the weight of the catalytic oxidation catalyst, the core weight is 70-90% of the catalyst weight, and the outer shell weight is 10-30% of the catalyst weight.

[0019] In a preferred embodiment, in the above-mentioned advanced oxidation treatment method for organic wastewater, the catalytic oxidation catalyst includes two levels of pores, wherein the size of the first level pores is less than 2 nm and the size of the second level pores is 2 to 20 nm; furthermore, the pore volume of the first level pores accounts for 60 to 90% of the total pore volume, and the pore volume of the second level pores accounts for 10 to 40% of the total pore volume.

[0020] In a preferred embodiment, in the above-mentioned advanced oxidation treatment method for organic wastewater, based on the weight of the catalytic oxidation catalyst, ferrous sulfide accounts for 5-20% of the catalyst weight, and copper oxide accounts for 2-10% of the catalyst weight.

[0021] In a preferred embodiment, the specific surface area of ​​the catalytic oxidation catalyst in the above-mentioned advanced oxidation treatment method for organic wastewater is 200–1200 m². 2 / g.

[0022] In a preferred embodiment, in the above-mentioned advanced oxidation treatment method for organic wastewater, the molar ratio of iron to copper in the catalytic oxidation catalyst is greater than 1.2:1.

[0023] In a preferred embodiment, in the above-mentioned advanced oxidation treatment method for organic wastewater, the pH value of the system after the reaction is completed can be adjusted to not less than 7 by adding an alkaline compound. The alkaline compound can be an inorganic base, specifically at least one of sodium hydroxide, ammonia, potassium hydroxide, etc.

[0024] Compared with the prior art, the advanced oxidation treatment method for organic wastewater provided by the present invention has one or more of the following advantages: (1) In the advanced oxidation treatment method for organic wastewater provided by the present invention, under wet oxidation reaction conditions, copper-based catalysts will dissolve copper ions during the reaction process. However, when the dissolved copper ions come into contact with the downstream outer support loaded with ferrous sulfide catalytic oxidation catalyst, they will be adsorbed and enriched on the surface by the catalyst, and undergo a displacement reaction with ferrous sulfide to generate copper sulfide and ferrous ions, which are more difficult to dissolve. Both copper sulfide and ferrous ions are good catalytic oxidation catalysts and can continue to play a catalytic role, which solves the problem of copper dissolution in the current use of copper-based catalysts and avoids secondary pollution. Moreover, the in-situ displacement reaction generates new catalysts, which improves the long-term effectiveness of the catalyst.

[0025] (2) In the advanced oxidation treatment method for organic wastewater provided by this invention, the catalytic oxidation catalyst used has a core-shell structure, with the outer support being mesoporous. This serves as both a reaction site for large organic molecules and a channel for reacting molecules, allowing small molecule pollutants to enter the inner layer. The inner support has a microporous structure, possessing a strong adsorption and enrichment capacity for pollutant molecules. It can enrich low-concentration pollutant molecules after reaction in the mesoporous region, thereby increasing the reaction driving force. This invention organically combines the metal active components. The copper ions dissolved from the copper oxide loaded in the inner layer can react with the in-situ generated nano-ferrous sulfide to generate copper sulfide and ferrous ions with catalytic oxidation activity. This solves the problem of copper dissolution in the current use of copper-based catalysts and makes the catalyst activity more long-lasting.

[0026] (3) In the advanced oxidation treatment method for organic wastewater provided by the present invention, wet oxidation process and advanced oxidation process are combined. Oxygen-containing gas and oxidant are introduced into wet oxidation unit and advanced oxidation unit respectively. On the one hand, it can more effectively match with the corresponding catalyst. The catalytic active component present after treatment in wet oxidation reactor is ferrous ions generated by displacement reaction. The concentration is low. Most of the oxygen-containing gas added earlier has been consumed and it is difficult to have an effective catalytic reaction with ferrous ions. At this time, the introduction of oxidants such as hydrogen peroxide can promote the occurrence of advanced oxidation reactions such as Fenton reaction. This part of ferrous ions can be fully utilized to degrade organic pollutants more thoroughly. Attached Figure Description

[0027] Figure 1 This is a pore size distribution diagram of the catalytic oxidation catalyst prepared in Example 3 of the present invention. Detailed Implementation

[0028] The preparation method of the present invention will be further illustrated below with reference to specific embodiments, but the scope of the present invention is not limited to the scope of these embodiments.

[0029] Unless otherwise expressly stated, throughout the specification and claims, the term "comprising" or its variations such as "including" or "comprising" shall be understood to include the stated elements or components without excluding other elements or other components.

[0030] In this document, the terms "first," "second," etc., are used to distinguish two different elements or parts, and are not used to define specific positions or relative relationships. In other words, in some embodiments, the terms "first," "second," etc., can also be used interchangeably.

[0031] All publications, patent applications, patents, and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings commonly understood by those skilled in the art. In case of conflict, the definitions in this specification shall prevail.

[0032] When this specification uses the prefixes “known to those skilled in the art,” “prior art,” or similar terms to derive materials, substances, methods, steps, apparatus, or components, the objects derived from such prefixes cover those commonly used in the art at the time of this application, but also include those that are not currently commonly used but will become generally recognized in the art as suitable for similar purposes.

[0033] In the context of this invention, all numerical values ​​of parameters (e.g., quantity or condition) should be understood to be modified by the term “about” in all cases, regardless of whether “about” actually appears before the numerical value.

[0034] In the context of this invention, "substantially" means that deviations that are acceptable or reasonable to those skilled in the art are permitted, such as deviations within ±5%, ±2%, ±1%, ±0.5%, or ±0.1%.

[0035] Unless otherwise specified, all percentages, parts, ratios, etc. mentioned in this instruction manual are based on weight, and the pressure is gauge pressure.

[0036] In the context of this invention, any two or more embodiments or aspects of this invention can be arbitrarily combined, and the resulting technical solutions are part of the original disclosure of this specification and also fall within the protection scope of this invention.

[0037] In the context of this specification, the copper-based catalyst can be prepared by impregnation. Example 1

[0038] Weigh out 200g of material with a specific surface area of ​​826m². 2 Commercial columnar activated carbon (g / g) was dried at 110℃. Based on its water absorption rate, a solution was prepared using Cu(NO3)2·3H2O and Ce(NO3)3·6H2O at a ratio of 6.0% CuO and 2.0% CeO2 by weight of the total catalyst. The activated carbon strips were impregnated with an equal volume of Cu-Ce solution for 2 hours, dried at 80℃, and calcined at 550℃ under a nitrogen atmosphere for 4 hours. After cooling to room temperature, the carbon was removed to obtain the copper-based catalyst Cat-A1. Example 2

[0039] Weigh out 200g of alumina carrier with a specific surface area of ​​230 m². 2 / g, according to its water absorption rate, Cu(CH3COO)2·H2O solution was prepared with CuO accounting for 5% of the total weight of the catalyst. The alumina support was impregnated with the solution in equal volume for 5 hours, dried at 80℃, and then calcined in a muffle furnace at 550℃ for 6 hours. After the temperature was reduced to room temperature, it was taken out to obtain the copper-based catalyst Cat-A2.

[0040] In the context of this specification, the method for preparing the catalytic oxidation catalyst includes the following steps: (1) The activated carbon particles were mixed with a soluble copper salt solution and then dried and calcined under anaerobic conditions to obtain material A; (2) Material A is added to a polyvinyl alcohol solution for treatment, and after drying, material B is obtained; (3) After the silicon source, additives, silica-alumina clay, binder, alcohol and water are mixed evenly, material C is obtained; (4) Mix material B and material C to react, and then wash, dry and calcine to obtain material D; (5) Dissolve ferrous sulfate in oxygen-free water, then add stabilizer and mix evenly under inert atmosphere, then add material D and mix evenly to obtain material E; (6) Under inert atmosphere protection, sulfur-containing compound, surfactant and water are mixed evenly and then slowly added to material E. The pH value of the system is adjusted to 6-8, the temperature is raised to 60-80℃ for reaction, and the catalyst product is obtained after drying and calcination.

[0041] In a preferred embodiment, in the above-mentioned method for preparing the catalytic oxidation catalyst, the activated carbon particles in step (1) are shaped activated carbon particles, and the shape of the activated carbon particles can be any one of irregular particles, cylindrical, spherical, clover, four-leaf clover, or toothed sphere.

[0042] In a preferred embodiment, in the above-mentioned method for preparing the catalytic oxidation catalyst, the activated carbon particles in step (1) have more than 90% of the pores smaller than 2 nm.

[0043] In a preferred embodiment, in the above-mentioned method for preparing the catalytic oxidation catalyst, the soluble copper salt in step (1) is one or more of copper sulfate, copper nitrate, copper chloride, and copper acetate, preferably copper nitrate.

[0044] In a preferred embodiment, in the above-mentioned method for preparing the catalytic oxidation catalyst, the drying temperature in step (1) is 60-110°C (preferably 70-90°C), and the drying time is 2-12h (preferably 3-5h).

[0045] In a preferred embodiment, in the above-mentioned method for preparing the catalytic oxidation catalyst, the calcination temperature under anaerobic conditions in step (1) is 400-800℃ (preferably 500-700℃), and the calcination time is 2-8h (preferably 3-4h).

[0046] In a preferred embodiment, in the above-mentioned method for preparing the catalytic oxidation catalyst, the concentration of the polyvinyl alcohol solution in step (2) is 0.1wt% to 2.0wt%. The polyvinyl alcohol solution is generally obtained by dissolving polyvinyl alcohol in water at 55 to 95°C. The use of temperature-sensitive polyvinyl alcohol to form steric hindrance protects the micropores from blockage during the in-situ formation of the mesoporous material and makes it easy to remove.

[0047] In a preferred embodiment, in the above-mentioned method for preparing the catalytic oxidation catalyst, the treatment in step (2) is a mixing treatment, preferably carried out under ultrasonic conditions, with the ultrasonic conditions being 40 kHz and the treatment lasting for 0.2 to 2 hours.

[0048] In a preferred embodiment, in the above-mentioned method for preparing the catalytic oxidation catalyst, the volume of the polyvinyl alcohol solution in step (2) is 0.7 to 1.0 times the volume of water absorbed by the activated carbon.

[0049] In a preferred embodiment, in the above-mentioned method for preparing the catalytic oxidation catalyst, the drying temperature in step (2) is 50-100°C (preferably 70-80°C), and the drying time is 3-8h (preferably 4-6h).

[0050] In a preferred embodiment, in the above-mentioned method for preparing the catalytic oxidation catalyst, the silicon source in step (3) is methyl orthosilicate and / or tetraethyl orthosilicate, preferably tetraethyl orthosilicate.

[0051] In a preferred embodiment, in the above-mentioned method for preparing the catalytic oxidation catalyst, the auxiliary agent in step (3) is at least one of dodecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, and octadecyltrimethylammonium bromide.

[0052] In a preferred embodiment, in the above-mentioned method for preparing the catalytic oxidation catalyst, the silica-alumina clay in step (3) is a nanoparticle with a diameter of 2 to 5 nm, wherein the sum of the contents of silicon oxide and aluminum oxide accounts for more than 65% of the total mass of the silica-alumina clay.

[0053] In a preferred embodiment, in the above-mentioned method for preparing the catalytic oxidation catalyst, the alcohol in step (3) is a small molecule alcohol, which may specifically be methanol and / or ethanol, preferably ethanol.

[0054] In a preferred embodiment, in the above-mentioned method for preparing the catalytic oxidation catalyst, the binder in step (3) is at least one of methylcellulose, ethylcellulose, carboxymethylcellulose, and hydroxypropylmethylcellulose.

[0055] In a preferred embodiment, in the above-mentioned method for preparing the catalytic oxidation catalyst, the mass ratio of the amount of silica-alumina clay to the amount of silicon source in step (3) is less than or equal to 1:6.

[0056] In a preferred embodiment, in the above-mentioned method for preparing the catalytic oxidation catalyst, the washing in step (4) is water washing, specifically washing with water several times at 70-90°C, specifically 1-4 times.

[0057] In a preferred embodiment, in the above-mentioned method for preparing the catalytic oxidation catalyst, the drying temperature in step (4) is 60-110°C (preferably 70-90°C), and the drying time is 2-12h (preferably 3-5h).

[0058] In a preferred embodiment, in the above-mentioned method for preparing the catalytic oxidation catalyst, the calcination in step (4) is carried out under oxygen-free conditions, the calcination temperature is 400-800℃ (preferably 500-700℃), and the calcination time is 2-8h (preferably 3-4h).

[0059] In a preferred embodiment, in the above-mentioned method for preparing the catalytic oxidation catalyst, the stabilizer in step (5) is at least one of starch and cellulose, wherein the starch can be at least one of sweet potato starch, corn starch, and potato starch; and the cellulose can be at least one of methylcellulose, ethylcellulose, carboxymethylcellulose, and hydroxypropylmethylcellulose.

[0060] In a preferred embodiment, in the above-mentioned method for preparing the catalytic oxidation catalyst, the sulfur-containing compound in step (6) is selected from at least one of sodium sulfide and thioacetamide (CH3CSNH2).

[0061] In a preferred embodiment, in the above-mentioned method for preparing the catalytic oxidation catalyst, the surfactant in step (6) is at least one of the Span series surfactants and the Tween series surfactants. Specifically, the Span series surfactant is at least one of Span 20, Span 40, Span 60, and Span 80; the Tween series surfactant can be at least one of Tween 20, Tween 40, Tween 60, and Tween 80.

[0062] In a preferred embodiment, in the above-mentioned method for preparing the catalytic oxidation catalyst, the drying in step (6) is carried out under oxygen-free conditions, preferably by rotary evaporation drying, with a drying temperature of 50-90°C and a drying time of 3-8h; preferably, the drying temperature is 70-80°C and the drying time is 4-6h.

[0063] In a preferred embodiment, in the above-mentioned method for preparing the catalytic oxidation catalyst, the calcination in step (6) is carried out under oxygen-free conditions, the calcination temperature is 300-700℃, and the calcination time is 2-8h; preferably, the calcination temperature is 400-600℃ and the calcination time is 3-4h.

[0064] In a preferred embodiment, in the above-mentioned method for preparing the catalytic oxidation catalyst, the molar ratio of the sulfur-containing compound and ferrous sulfate added is 1.2:1 to 1:1.

[0065] In a preferred embodiment, in the above-mentioned method for preparing the catalytic oxidation catalyst, the separation in step (6) is a solid-liquid separation, which can be any of the existing methods in the art that can achieve solid-liquid two-phase separation, such as filtration or centrifugal separation.

[0066] The prepared catalytic oxidation catalyst has two active components. Ferrous sulfide not only catalyzes the generation of highly reactive free radicals from the oxidant but also acts as a co-catalyst, synergistically reacting with transition metal oxides to enhance pollutant removal. The catalyst's application involves a two-stage catalytic reaction: first, oxidant and pollutant molecules react with the outer ferrous sulfide layer, consuming a portion of them; then, the concentrations of oxidant and organic pollutants in contact with copper oxide through the pores are reduced, allowing for further catalytic degradation of pollutants through a more potent catalytic reaction with the copper oxide. Example 3

[0067] 70g of granular activated carbon was weighed and impregnated in a copper salt solution at a copper oxide to activated carbon mass ratio of 1:8.8. The copper salt was copper chloride. After drying at 80℃ for 5h, the sample was calcined at 500℃ for 4h in a tube furnace under nitrogen protection to obtain material A. Material A was added to 50mL of 0.5% polyvinyl alcohol solution and ultrasonically vibrated for 1.5h, then dried at 80℃ for 4h to obtain material B. 4g of nano-aluminosilicate clay, 1.0g of methylcellulose, 2.2g of dodecyltrimethylammonium bromide, 25g of tetraethyl orthosilicate, 100mL of water, and 50mL of ethanol were mixed to obtain material C. Material B was placed in material C and stirred continuously. After reacting at room temperature (25℃) for 3h, rotary evaporation was performed to obtain... The sample was washed with 80℃ hot water, dried at 75℃, and calcined at 500℃ for 3 hours under nitrogen protection to obtain material D. Ferrous sulfate was dissolved in distilled water to prepare a 0.68mol / L ferrous sulfate solution. 200mL of ferrous sulfate solution was added to 0.1g of sweet potato starch and mixed evenly under nitrogen protection. Material D was added to the solution and fully impregnated to obtain material E. 0.03g of Tween 40 was added to a 1.4mol / L thioacetamide solution and mixed evenly. The mixture was slowly added to material E under nitrogen protection. The pH of the system was adjusted to 7.5, and the reaction was carried out at 75℃ for 1.5 hours. Excess moisture was removed by rotary evaporation at 80℃. The catalyst Cat-B1 was obtained by calcination in a tube furnace at 450℃ under nitrogen protection for 3 hours. Example 4

[0068] Weigh 65g of granular activated carbon and impregnate it in a copper salt solution at a copper oxide to activated carbon mass ratio of 1:9.3. The copper salt is copper nitrate. Dry at 75℃ for 5 hours, then calcine at 600℃ for 4 hours under nitrogen protection in a tube furnace to obtain material A. Add material A to 55ml of a 0.5% polyvinyl alcohol solution, ultrasonically vibrate for 40 minutes, and then dry at 80℃ for 4.5 hours to obtain material B. Mix 5g of nano-alumina silica clay, 1.5g of carboxymethyl cellulose, 3.6g of hexadecyltrimethylammonium bromide, 62g of tetraethyl orthosilicate, 60ml of water, and 40ml of ethanol to obtain material C. Place material B in material C and stir continuously. React at room temperature for 2.5 hours, then evaporate the polyvinyl chloride in an 85℃ water bath. The excess water was washed with hot water at 85℃, dried at 80℃, and calcined at 550℃ for 4 hours under nitrogen protection to obtain material D. Ferrous sulfate was dissolved in distilled water to prepare a 0.76mol / L ferrous sulfate solution. 150ml of ferrous sulfate solution was added to 0.1g of methylcellulose and stirred evenly under nitrogen protection. Material D was added to the solution and fully impregnated to obtain material E. 0.01g of Tween 80 was added to a 0.6mol / L sodium sulfide solution and mixed evenly. The solution was slowly added to material E under nitrogen protection. The pH of the system was adjusted to 8.0, and the reaction was carried out at 78℃ for 1.2 hours. Excess water was removed by rotary evaporation at 75℃. The catalyst Cat-B2 was obtained by calcination in a tube furnace at 500℃ under nitrogen protection for 3 hours. Example 5

[0069] 81g of spherical activated carbon was weighed and impregnated in a copper salt solution (copper nitrate was selected as the copper salt) at a copper oxide to activated carbon mass ratio of 1:20.3. The carbon was dried at 90℃ for 3.5h and calcined at 550℃ for 4h under nitrogen protection in a tube furnace to obtain material A. Material A was added to 60ml of a 1.3% (w / w) polyvinyl alcohol solution, ultrasonically vibrated for 45min, and then dried at 80℃ for 5h to obtain material B. 1g of nano-alumina silica clay, 3.0g of carboxymethyl cellulose, 2.5g of dodecyltrimethylammonium bromide, 31g of tetraethyl orthosilicate, 150ml of water, and 50ml of ethanol were mixed to obtain material C. Material B was placed in material C and stirred continuously. After reacting at room temperature for 5h, rotary evaporation was performed to obtain the sample. The product was washed with 85℃ hot water, dried at 80℃, and calcined at 650℃ for 4 hours under nitrogen protection to obtain material D. Ferrous sulfate was dissolved to prepare a 1.36mol / L ferrous sulfate solution. 50ml of the ferrous sulfate solution was added to 0.05g of carboxymethyl cellulose and stirred evenly under nitrogen protection. Material D was added to the solution and fully impregnated to obtain material E. 0.01g of Span 80 was added to a 1.4mol / L thioacetamide solution and mixed evenly. The mixture was slowly added to the above system under nitrogen protection. The pH of the system was adjusted to 8.0, and the reaction was carried out at 65℃ for 2 hours. Excess moisture was removed by rotary evaporation at 75℃. The catalyst Cat-B3 was obtained by calcination in a tube furnace at 520℃ under nitrogen protection for 3.5 hours.

[0070] Comparative Example 1 The preparation process is basically the same as in Example 3, except that material A is not impregnated with polyvinyl alcohol solution to obtain catalyst Cat-C1.

[0071] Comparative Example 2 Weigh 65g of granular activated carbon and add it to 55ml of 0.5% polyvinyl alcohol solution. Sonicate for 40min, then dry at 80℃ for 3h to obtain material A. Mix 5g of nano-aluminosilicate clay, 1.5g of carboxymethyl cellulose, 3.6g of hexadecyltrimethylammonium bromide, 60g of tetraethyl orthosilicate, 60ml of water, and 40ml of ethanol to obtain material B. Place material A in material B and stir continuously. React at room temperature for 2.5h, then evaporate excess water in an 85℃ water bath. Wash with 85℃ hot water, dry at 80℃, and calcine at 550℃ for 4h under nitrogen protection to obtain material C. Impregnate material C with a copper salt solution at a copper oxide to activated carbon mass ratio of 1:9.3. Select copper salt... Copper nitrate was dried at 75℃ for 5 hours and calcined in a tube furnace at 600℃ for 4 hours under nitrogen protection to obtain material D. Ferrous sulfate was dissolved in distilled water to prepare a 0.76 mol / L ferrous sulfate solution. 150 ml of the ferrous sulfate solution was added to 0.1 g of methylcellulose and stirred evenly under nitrogen protection. Material D was added to the solution and fully impregnated to obtain material E. 0.01 g of Tween 80 was added to a 0.6 mol / L sodium sulfide solution and mixed evenly. The solution was slowly added to material E under nitrogen protection. The pH of the system was adjusted to 8.0, and the reaction was carried out at 78℃ for 1.2 hours. Excess moisture was removed by rotary evaporation at 75℃. The catalyst Cat-C2 was obtained by calcination in a tube furnace at 500℃ under nitrogen protection for 3 hours. Example 6

[0072] Copper-based catalyst Cat-A1 and catalytic oxidation catalyst Cat-B1 were loaded into a wet oxidation reactor at a volume ratio of 4:6, with a total catalyst volume of 100 cm³. 3 Simulated acrylic acid wastewater (initial COD value of 23600 mg / L) flows into the bottom of a wet oxidation reactor. The reactor temperature is 210℃, the reaction pressure is 4.4 MPa, and excess oxygen is used as the oxidant. The oxygen and wastewater are mixed and preheated before entering the reactor, and the reaction space velocity is 1 h⁻¹. -1 The organic wastewater treated by the wet oxidation reactor flows into an ambient temperature and pressure reactor, where hydrogen peroxide is introduced as an oxidant at a dosage of 10 g / L. The pH is adjusted to 3.5 for the reaction. The effluent is then adjusted to pH 10.5 for sedimentation. The measured COD is 2772 mg / L and the copper ion concentration is 217 μg / L. Example 7

[0073] Copper-based catalyst Cat-A1 and catalytic oxidation catalyst Cat-B2 were loaded into a wet oxidation reactor at a volume ratio of 5:5, with a total catalyst volume of 120 cm³. 3Simulated acrylic acid wastewater (initial COD value of 23600 mg / L) flows into the bottom of a wet oxidation reactor. The reactor temperature is 240℃, the reaction pressure is 5.2 MPa, and air is used as the oxidant in excess. The air is mixed and preheated with the wastewater before entering the reactor, and the reaction space velocity is 0.5 h⁻¹. -1 The organic wastewater treated by the wet oxidation reactor flows into an ambient temperature and pressure reactor, where hydrogen peroxide is introduced as an oxidant at a dosage of 8 g / L. The pH is adjusted to 2.8 for reaction. The effluent is then adjusted to pH 10.0 for sedimentation. The measured COD is 1826 mg / L and the copper ion concentration is 221 μg / L. Example 8

[0074] Copper-based catalyst Cat-A1 and catalytic oxidation catalyst Cat-B3 were loaded into a wet oxidation reactor at a volume ratio of 3:7, with a total catalyst volume of 80 cm³. 3 Acetophenone-based simulated wastewater (initial COD value of 15280 mg / L) flowed into the bottom of the first reactor. The reactor temperature was 240℃, and the reaction pressure was 5.6 MPa. Oxygen was used as the oxidant. Excess oxygen was mixed and preheated with the wastewater at the bottom of the reactor before passing through the catalyst bed for catalytic wet oxidation. The reaction space velocity was 0.75 h⁻¹. -1 Organic wastewater flows into a reactor at ambient temperature and pressure, and hydrogen peroxide is introduced as an oxidant at a dosage of 7 g / L. The pH is adjusted to 3.0 for the reaction to proceed. The pH of the effluent is adjusted to 10.2 for sedimentation. The measured COD is 1986 mg / L and the copper ion concentration is 358 μg / L. Example 9

[0075] Copper-based catalyst Cat-A2 and catalytic oxidation catalyst Cat-B1 were loaded into a wet oxidation reactor at a volume ratio of 5:5, with a total catalyst volume of 120 cm³. 3 Simulated acrylic acid wastewater (initial COD value of 30940 mg / L) flows into the bottom of the first reactor. The reactor temperature is 270℃, the reaction pressure is 7.5 MPa, and oxygen is used as the oxidant. Excess oxygen is mixed and preheated with the wastewater at the bottom of the reactor before passing through the catalyst bed for catalytic wet oxidation. The reaction space velocity is 0.75 h⁻¹. -1 Organic wastewater flows into a reactor at ambient temperature and pressure, and hydrogen peroxide is introduced as an oxidant at a dosage of 12.5 g / L. The pH is adjusted to 3.6 for the reaction to proceed. The pH of the effluent is adjusted to 10.8 for sedimentation. The measured COD is 3712 mg / L and the copper ion concentration is 472 μg / L. Example 10

[0076] Copper-based catalyst Cat-A2 and catalytic oxidation catalyst Cat-B2 were loaded into a wet oxidation reactor at a volume ratio of 6:4, with a total catalyst volume of 100 cm³. 3 Simulated wastewater containing α,α-dimethylbenzyl alcohol (initial COD value of 5400 mg / L) flowed into the bottom of a wet oxidation reactor. The reactor temperature was 230℃, and the reaction pressure was 5.5 MPa. Air was used as the oxidant. Excess oxygen was mixed and preheated with the wastewater at the bottom of the reactor before passing through the catalyst bed for catalytic wet oxidation. The reaction space velocity was 1.5 h⁻¹. -1 Organic wastewater flows into a reactor at ambient temperature and pressure, and hydrogen peroxide is introduced as an oxidant at a dosage of 2.5 g / L. The pH is adjusted to 4.3 for the reaction to proceed. The pH of the effluent is adjusted to 9.2 for sedimentation. The measured COD is 623 mg / L and the copper ion concentration is 183 μg / L. Example 11

[0077] Copper-based catalyst Cat-A1 and catalytic oxidation catalyst Cat-B2 were loaded into a wet oxidation reactor at a volume ratio of 5:5, with a total catalyst volume of 120 cm³. 3 Simulated acrylic acid wastewater (initial COD value of 23600 mg / L) flows into the bottom of a wet oxidation reactor. The reactor temperature is 240℃, the reaction pressure is 5.2 MPa, and air is used as the oxidant in excess. The air is mixed and preheated with the wastewater before entering the reactor, and the reaction space velocity is 0.5 h⁻¹. -1 The COD of the effluent from the reaction was measured to be 3227 mg / L, and the copper ion concentration was 289 μg / L.

[0078] Comparative Example 3 Example 6 was repeated, but the catalytic oxidation catalyst Cat-B1 was replaced with Cat-C1, and other conditions remained unchanged. The COD was measured to be 2936 mg / L and the copper ion concentration was 1382 μg / L.

[0079] Comparative Example 4 Example 10 was repeated, but the catalytic oxidation catalyst Cat-B2 was replaced with Cat-C2, and other conditions remained unchanged. The COD was measured to be 975 mg / L and the copper ion concentration was 994 μg / L.

[0080] Comparative Example 5 The copper-based catalyst Cat-A1 was loaded into a wet oxidation reactor, with a total catalyst volume of 80 cm³. 3 Acetophenone-based simulated wastewater (initial COD value of 15280 mg / L) flowed into the reactor from the bottom. The reactor temperature was 240℃, and the reaction pressure was 5.6 MPa. Oxygen was used as the oxidant. Excess oxygen was mixed and preheated with the wastewater at the bottom of the reactor before passing through the catalyst bed for catalytic wet oxidation. The reaction space velocity was 0.75 h⁻¹.-1 Organic wastewater flows into a reactor at ambient temperature and pressure, and hydrogen peroxide is introduced as an oxidant at a dosage of 7 g / L. The pH is adjusted to 3.0 for the reaction to proceed. The pH of the effluent is adjusted to 10.2 for sedimentation. The measured COD is 2726 mg / L and the copper ion concentration is 2231 μg / L.

[0081] Comparative Example 6 The catalytic oxidation catalyst Cat-B1 was loaded into a wet oxidation reactor, with a total catalyst volume of 120 cm³. 3 Simulated acrylic acid wastewater (initial COD value of 30940 mg / L) flows into the reactor from the bottom. The reactor temperature is 270℃, and the reaction pressure is 7.5 MPa. Oxygen is used as the oxidant. Excess oxygen is mixed and preheated with the wastewater at the bottom of the reactor before passing through the catalyst bed for catalytic wet oxidation. The reaction space velocity is 0.75 h⁻¹. -1 Organic wastewater flows into a reactor at ambient temperature and pressure, and hydrogen peroxide is introduced as an oxidant at a dosage of 12.5 g / L. The pH is adjusted to 3.6 for the reaction to proceed. The pH of the effluent is adjusted to 10.8 for sedimentation. The measured COD is 5231 mg / L and the copper ion concentration is 391 μg / L.

Claims

1. A method for advanced oxidation treatment of organic wastewater, the method comprising the following: In the presence of oxygen-containing gas, organic wastewater enters the wet oxidation reactor for reaction. According to the contact sequence with the organic wastewater, the wet oxidation reactor is sequentially filled with copper-based catalyst and catalytic oxidation catalyst. Copper-based catalysts consist of a support and an active metal component, with the active metal component distributed on the support. The support is selected from one or more of activated carbon, molecular sieves, and inorganic oxides. The active metal component is copper, and its content, calculated as an oxide, ranges from 1 wt% to 20 wt%. The catalytic oxidation catalyst has a core-shell structure, in which the core is activated carbon supported with copper oxide and ferrous sulfide, and the outer shell is silicon oxide supported with nano-ferrous sulfide. The outer support has a mesoporous structure, and the inner support has a microporous structure. The catalytic oxidation catalyst includes two levels of channels, in which the size of the first level channel is less than 2 nm, and the size of the second level channel is 2 to 20 nm.

2. A method for advanced oxidation treatment of organic wastewater, the method comprising the following: In the presence of oxygen-containing gas, organic wastewater enters a wet oxidation reactor for reaction. According to the contact sequence with the organic wastewater, copper-based catalyst and catalytic oxidation catalyst are sequentially loaded into the wet oxidation reactor. The liquid phase material obtained after treatment by the wet oxidation reactor comes into contact with the oxidant for reaction. After the reaction is completed, the pH value of the system is adjusted to be no less than 7 and sedimentation treatment is carried out. Copper-based catalysts consist of a support and an active metal component, with the active metal component distributed on the support. The support is selected from one or more of activated carbon, molecular sieves, and inorganic oxides. The active metal component is copper, and its content, calculated as an oxide, ranges from 1 wt% to 20 wt%. The catalytic oxidation catalyst has a core-shell structure, in which the core is activated carbon supported with copper oxide and ferrous sulfide, and the outer shell is silicon oxide supported with nano-ferrous sulfide. The outer support has a mesoporous structure, and the inner support has a microporous structure. The catalytic oxidation catalyst includes two levels of channels, in which the size of the first level channel is less than 2 nm, and the size of the second level channel is 2 to 20 nm.

3. The advanced oxidation treatment method for organic wastewater according to claim 1 or 2, wherein, The COD value of the organic wastewater is 5000-50000 mg / L, and the organic wastewater is any one or more of refining wastewater, chemical wastewater and municipal wastewater.

4. The advanced oxidation treatment method for organic wastewater according to claim 1 or 2, wherein, The oxygen-containing gas has an oxygen volume content of 20% to 100%; the oxygen-containing gas is selected from at least one of air, oxygen, and a mixture of oxygen and an inert gas.

5. The advanced oxidation treatment method for organic wastewater according to claim 1 or 2, wherein, Before entering the wet oxidation reactor, the oxygen-containing gas is mixed and preheated with the organic wastewater to 100-200°C.

6. The advanced oxidation treatment method for organic wastewater according to claim 1 or 2, wherein, The reaction conditions in the wet oxidation reactor are as follows: reaction temperature 150–350℃, pressure 4–15 MPa, and space velocity 0.25–3.0 h⁻¹. -1 .

7. The advanced oxidation treatment method for organic wastewater according to claim 1 or 2, wherein, The amount of oxygen-containing gas used should be more than 1.0 times the amount of oxidant required based on the COD value of the organic wastewater raw material.

8. The advanced oxidation treatment method for organic wastewater according to claim 2, wherein, The oxidizing agent is one or more of hydrogen peroxide, ozone, and persulfate.

9. The advanced oxidation treatment method for organic wastewater according to claim 2 or 8, wherein, The oxidizing agent is hydrogen peroxide.

10. The advanced oxidation treatment method for organic wastewater according to claim 8, wherein, Persulfate is at least one of sodium persulfate, potassium persulfate, ammonium persulfate, and potassium peroxymonosulfate.

11. The advanced oxidation treatment method for organic wastewater according to claim 2, wherein, The amount of oxidant used is 0.2 to 0.5 times the chemical oxygen demand of the organic wastewater.

12. The advanced oxidation treatment method for organic wastewater according to claim 2, wherein, When the liquid phase feed obtained after treatment by the wet oxidation reactor comes into contact with the oxidant for reaction, the pH value of the reaction system is controlled to be 2-5.

13. The advanced oxidation treatment method for organic wastewater according to claim 1 or 2, wherein, The volume ratio of copper-based catalyst to catalytic oxidation catalyst is 20%–60%: 40%–80%.

14. The advanced oxidation treatment method for organic wastewater according to claim 1 or 2, wherein, The volume ratio of copper-based catalyst to catalytic oxidation catalyst is 30%–50%: 50%–70%.

15. The advanced oxidation treatment method for organic wastewater according to claim 1 or 2, wherein, The molecular sieve is one or more of type A, type Y, Beta, ZSM-5, and TS-1 molecular sieves, and the inorganic oxide is one or more of alumina, silicon dioxide, cerium dioxide, and titanium dioxide.

16. The advanced oxidation treatment method for organic wastewater according to claim 1 or 2, wherein, The copper-based catalyst includes an auxiliary component, which is one or more of iron, nickel, manganese, cobalt, zinc, lanthanum, cerium, tin, and molybdenum, and the content of the auxiliary component, calculated as oxide, is 0.1 to 5 wt%.

17. The advanced oxidation treatment method for organic wastewater according to claim 1 or 2, wherein, Based on the weight of the catalytic oxidation catalyst, the core weight is 70-90% of the catalyst weight, and the outer shell weight is 10-30% of the catalyst weight.

18. The advanced oxidation treatment method for organic wastewater according to claim 1 or 2, wherein, The volume of the first-level channel accounts for 60-90% of the total volume, and the volume of the second-level channel accounts for 10-40% of the total volume.

19. The advanced oxidation treatment method for organic wastewater according to claim 1 or 2, wherein, Based on the weight of the catalytic oxidation catalyst, ferrous sulfide accounts for 5-20% of the catalyst weight, and copper oxide accounts for 2-10% of the catalyst weight.

20. The advanced oxidation treatment method for organic wastewater according to claim 1 or 2, wherein, The specific surface area of ​​the catalytic oxidation catalyst is 200–1200 m². 2 / g.

21. The advanced oxidation treatment method for organic wastewater according to claim 1 or 2, wherein, The molar ratio of iron to copper in the catalytic oxidation catalyst is greater than 1.2:1.

Citation Information

Patent Citations

  • Preparation method of copper-based wet oxidation catalyst

    CN108940301A

  • Treatment method and application of sulfur-containing wastewater

    CN111056612A

  • Method of treating organic waste water by adopting Fe / FeS composite material activated dioxygen

    CN104291435A

  • Metal carrying catalyst and method for treating water using the same

    JP2002301377A